FEATURES OF TOURISM GROWTH IN UZBEKISTAN: BASED ON FOREIGN EXPERIENCE - Sharipova Umida (Scholar Express Journals, 2023)
The article is devoted to the development of e-tourism in Uzbekistan, which contributes to the development of the services sector not only in the country, but also in the global economy. It is shown that without work on problems in the tourism sector in Uzbekistan, we will not be able to increase the potential of the country. As examples of how a country with a developed e-tourism infrastructure in the tourism sector were chosen ASEAN countries. The main goal now is the development of electronic services through some resources.
Keywords: Tourism; electronic tourism; electronic tourismtraveler